Little Red Riding Hood asks about defense planning. Some answers and the NATO case. - CASTILLA BAREA, Juan Carlos (Journal of the Spanish Institute for Strategic Studies, 2022)
The «defence planning» is a process of the defence public policy, incardinated with the National Security Strategy, in which internal and external requirements are considered. Coherence must be ensured from top to bottom and vice versa. In this planning, formulation and implementation of part of the «defence policy» converge. Starting from a political "level of ambition" for the military instrument, hypothesis-based planning scenarios are used, to which to respond, and from which capacity requirements are inferred, to face the future risks. There are four types of planning: “mobilization”, “threat based”, “portfolio”, and “capability based”. This article introduces the “NATO Defence Planning Process” (NDPP), as an example of the «portfolio» type, and based on the "NATO Warfighting Capstone Concept" (NWCC), it offers some guidelines on the configuration of future planning scenarios.